Analyzing the Effectiveness of Network-Centric Warfare-Based Defence Strategies In Responding to Asymmetric Threats: A Quantitative Approach - Toni Toni; Asep Adang Supriyadi (PERSPEKTIF, 2025)
This study examines the impact of Network-Centric Warfare (NCW)-based defence strategies on military effectiveness in countering asymmetric threats. Focusing on three critical dimensions—Information and Communication Integration, Command-and-Control (C2) Interoperability, and Adaptive & AI-Capable NCW Systems—the research adopts a quantitative methodology using Structural Equation Modeling (SEM) to assess their influence. Asymmetric threats, characterized by unpredictable, unconventional tactics, require military forces to adapt rapidly and operate with high coordination. The findings indicate that NCW-based strategies significantly enhance military capabilities in terms of responsiveness, adaptability, and operational coordination. The integration of real-time information and communication technologies enables better situational awareness and informed decision-making. C2 interoperability ensures seamless collaboration among units and branches, while adaptive systems enhanced with artificial intelligence provide strategic advantages in dynamic conflict environments. This study highlights the importance of transitioning from traditional, platform-centric models to network-enabled operations, thereby enabling effective responses to contemporary security challenges. The empirical evidence supports the strategic value of NCW in enhancing combat readiness and operational performance. By validating these relationships, the study contributes to the body of knowledge on defence innovation. It offers practical insights for military planners and policymakers in strengthening national security through technology-driven strategies.